Data science and analytics - Kumari, Sneha; Tripathy, K. K.; Kumbhar, Vidya (Emerald Publishing Limited, 2020)
Data Science and Analytics explores the application of big data and business analytics by academics, researchers, industrial experts, policy makers and practitioners, helping the reader to understand how big data can be efficiently utilized in better managerial applications.